Early Renin Recovery After Adrenalectomy in Aldosterone-Producing Adenomas: A Prospective Study - Mermejo, Livia M.; Elias, Paula C.L.; Molina, Carlos A.F.; Tucci, Silvio; Muglia, Valdair F.; Elias, Jorge; Antonini, Sonir R.; de Castro, Margaret; Moreira, Ayrton C. (Hormone and Metabolic Research, 2022)
The aim of the study was to clarify the relationship and the time of aldosterone and renin recoveries at immediate and long-term follow-up in aldosterone-producing adenoma (APA) patients who underwent adrenalectomy. Prospective and longitudinal protocol in a cohort of APA patients was followed in a single center. Among 43 patients with primary aldosteronism (PA), thirteen APA patients were enrolled in this study. Blood was collected for aldosterone, renin, potassium, creatinine, cortisol, and ACTH before and 1, 3, 5, 7, 15, 30, 60, 90, 120, 180, 270, 360 days after adrenalectomy. At diagnosis, most patients (84%) had hypokalemia and high median aldosterone levels (54.8; 24.0–103 ng/dl) that decreased to undetectable (<2.2) or very low (<3.0) levels between fifth to seventh days after surgery; then, between 3–12 months, its levels gradually increased to the lower normal range. The suppressed renin (2.3; 2.3–2.3 mU/l) became detectable between the fifteen and thirty days after surgery, remaining normal throughout the study. The aldosterone took longer than renin to recover (60 vs.15 days; p<0.002) and patients with higher aldosterone had later recovery (p=0.03). The cortisol/ACTH levels remained normal despite the presence of a post-operative hypoaldosteronism. Blood pressure and antihypertensive requirement decreased after adrenalectomy. In conclusion, our prospective study shows the borderline persistent post-operative hypoaldosteronism in the presence of early renin recovery indicating incapability of the zona glomerulosa of the remaining adrenal gland to produce aldosterone. These findings contribute to the comprehension of differences in renin and aldosterone regulation in APA patients, although both are part of the same interconnected system.
Keywords: renin-aldosterone relationship; primary aldosteronism; APA; adrenalectomy